Understanding the Roots of Latina Migrants' Captivity - Escobar, Martha D. (Social justice, 2009)
This essay discusses the history of the use of prisons in the United States to organize society from the 1970s through 2010, particularly with regard to Latinos. Since changes in the enforcement of immigration laws, Latinos have become the largest ethnic group in the federal prison system. The article focuses on border control between the U.S. and Mexico and the general criminalization of Latino immigrants and especially Latina immigrants.